Margin within margin: a morphosyntactic approach of ain’t versus innit - Isabelle GAUDY-CAMPBELL (E-REA)
Ain’t and innit are two invariant non-standard markers. Through a morphosyntactic approach, and focusing on the contexts where they are both tags, the article compares the two marginal forms with their standard equivalents. In comparison to grammatically dependent tags, they can function as multi-operators. Compared to each other, those two clitics have different features with innit actually containing ain’t according to former derivational morphology studies. Rather than limiting ourselves to a restricted approach, it seems more relevant to consider them within a wider context. Ain’t is more than a mere predicate. In some contexts, it codes the orality of a passage. Innit works very much as a discourse marker and can be categorised as a thetical. They thereby have distinct invariant functions. Far from being a lesser version of the standard auxiliaries, these so-called non-standard forms go beyond their standard equivalent.